EMPOWERING POSYANDU LANSIA GROUP THROUGH LOCAL FOOD PROCESSING TRAINING FOR PREVENTION OF DIABETES - Putri, Enda Silvia; Marniati, Marniati; Khairunnas, Khairunnas; Mulyani, Itza; Siregar, Siti Maisyaroh Fitri; Anwar, Sufyan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The proportion of cases of Diabetes Mellitus (DM) in the region of West Aceh is still quite high especially in the two Health Center/Puskesmas in the City of Meulaboh namely Suakribe and Meureubo in 2021 on average 83% to 84% in 2022. The risk factors for DM in Aceh, based on the initial survey, are mostly due to dietary factors, such as inadequate local food processing that puts DM at risk. The purpose of the dedication is to enhance the skills of posyandu lansia groups in processing local food for prevention of diabetes. Implementation method with training processing of local food products, such as mie and cookies based on sunti aceh, taro, corn, carrots, and potatoes to 13 posyandu lansia group of 7 cadre/kader and 6 old man/lansia. The result was an increase in knowledge and skills of cadre and old man with P Value ≤ α = 0.05 in terms of local food processing for prevention of diabetes (processing mie and cookies). The conclusion of the training is able to enhance the knowledge and skills of respondents in terms of local food processing for prevention of diabetes. Recommendations Local food training is very well done to communities specialized in member of posyandu (cadre/kader and old man/lansia) in an effort to increase independence in processing local foods that can prevent diabetes.